2011
DOI: 10.1097/jnn.0b013e318234ea24
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise-Based Rehabilitation on Balance and Gait for Stroke Patients

Abstract: This review evaluated the effects of balance and/or gait exercise interventions for stroke survivors and summarized the available evidence on these exercise interventions. A search for studies published between January 2001 and January 2010 was performed using the keywords stroke, walking or balance, and physical activity or exercise. Seventeen randomized clinical trials were identified. The findings suggest that initiating early rehabilitation during acute to subacute stroke recovery can improve balance and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 19 publications
2
41
0
3
Order By: Relevance
“…It is estimated that 3-6 months after stroke, approximately 15% -40% of the victims will be unable to walk independently at home and only 18% will show skills to walk with no restriction [11] [39] [49]. A review performed in the United Kingdom revealed that about 50% of all stroke survivors will still have severe functional deficits six months after stroke onset and approximately 53% will still depend on other people to perform DLA [11]. Although recent studies in neuroscience and clinical research have demonstrated that the brain is able to significantly recover after a stroke [5], according to CPGMSR 40% of stroke victims will show a moderate functional impairment, 30% -50% severe incapacity and 15% -30% persistent deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that 3-6 months after stroke, approximately 15% -40% of the victims will be unable to walk independently at home and only 18% will show skills to walk with no restriction [11] [39] [49]. A review performed in the United Kingdom revealed that about 50% of all stroke survivors will still have severe functional deficits six months after stroke onset and approximately 53% will still depend on other people to perform DLA [11]. Although recent studies in neuroscience and clinical research have demonstrated that the brain is able to significantly recover after a stroke [5], according to CPGMSR 40% of stroke victims will show a moderate functional impairment, 30% -50% severe incapacity and 15% -30% persistent deficits.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the leading causes of morbimortality in most of developed and developing countries, being also considered the most important cause of disability worldwide [6]. It is estimated that 3-6 months after stroke, approximately 15% -40% of the victims will be unable to walk independently at home and only 18% will show skills to walk with no restriction [11] [39] [49]. A review performed in the United Kingdom revealed that about 50% of all stroke survivors will still have severe functional deficits six months after stroke onset and approximately 53% will still depend on other people to perform DLA [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke diagnosis and location of lesions were based on computed tomography or magnetic resonance imaging as well as neurological functions. Inclusion criteria were as follows: (1) discharge from rehabilitation services after unilateral stroke 6 to 18 months earlier, (2) an ischemic or hemorrhagic poststroke hemiplegia, (3) a score of at least 26 on the Korean version of the modified mini-mental status examination, (4) no excessive spasticity in the more affected arm, (5) able to reach Brunnstrom stage III or above in the proximal and distal parts of the arms, (6) no excessive pain in the more affected UE. 17 The degree of spasticity and pain was measured using the modified Ashworth spasticity (MAS) scale and a 10-point visual analog scale (VAS), respectively.…”
Section: Subjectsmentioning
confidence: 99%
“…Previous studies have demonstrated the trainability of patients with stroke and documented the beneficial strength and functional effects of various types of rehabilitation, 6 of which, whole-body vibration (WBV) has emerged and has been investigated as a rehabilitation and complementary method in older adults 7,8 and patients with hemiplegic stroke. 9,10 There have also been numerous studies examining the potential therapeutic effects of WBV.…”
mentioning
confidence: 99%